2008
DOI: 10.1021/bi801116k
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Conjugation Enhances the Nitrite Reductase Activity of Native and Cross-Linked Hemoglobin

Abstract: Although stabilized hemoglobins have been evaluated as oxygen-carrying replacements for red cells in transfusions, in vivo evaluations have noted that these materials are associated with vasoactivity, a serious complication. Scavenging of endogenous nitric oxide by the deoxyheme sites of the stabilized proteins is one likely source of vasoactivity. Recent reports indicate that modification of cell-free hemoglobin derivatives with multiple chains of polyethylene glycol (PEG) suppresses vasoactivity. Gladwin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 24 publications
2
55
0
1
Order By: Relevance
“…In this work we demonstrate the effects of various methods of hemoglobin crosslinking and conjugation on the protein's nitrite reductase activity (60). We show that PEG-hemoglobins react at enhanced rates to produce NO, a reaction that is related to the protein's affinity and cooperativity for oxygen binding and release.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In this work we demonstrate the effects of various methods of hemoglobin crosslinking and conjugation on the protein's nitrite reductase activity (60). We show that PEG-hemoglobins react at enhanced rates to produce NO, a reaction that is related to the protein's affinity and cooperativity for oxygen binding and release.…”
Section: Discussionmentioning
confidence: 89%
“…follows that an HBOC with an increased molecular size, high affinity and cooperativity for oxygen and enhanced nitrite reductase activity will have some of the necessary properties for a safe blood substitute. We have now shown that the addition of PEG to hemoglobin at β-Cys93 significantly increases the rate of reduction of nitrite to NO compared to native and cross-linked hemoglobin (60). The increased rate of NO production may therefore also contribute to the decreased hypertensive effect observed with larger PEGylated hemoglobins (39,55,58,67,68).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other reactions and mechanisms are still under investigation (30, 36, 89 -91). Nonetheless, there are clear indications of the role of this reaction as seen in studies that show that the efficacy of potential Hb-based oxygen carriers are correlated with nitrite reductase activity (92)(93)(94).…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, esses procedimentos são laboriosos e requerem, em geral, 1 hora para obter curva de processo de reação [154,157] A Figura 63 mostra a relação entre a intensidade de corrente amostrada em -1,1 V e a concentração de NaNO 2 para cada um dos seis filmes estudados. Entretanto, a falta de reticulação em estrutura da Hb-PEG5K 2 desfavorece a sua aplicabilidade clínica pelo seu potencial risco de dissociação em espécies diméricas in vivo.…”
Section: Objetivosunclassified